The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/jcu.22227
|View full text |Cite
|
Sign up to set email alerts
|

Procedural sedation and analgesia as an adjunct to periprostatic nerve block for prostate biopsy: A prospective randomized trial

Abstract: PSAA with midazolam and remifentanil used as an adjunct to the standard PNB is safe and effective during TRUS-PB. Patients undergoing PSAA in addition to PNB experienced significantly less pain and higher satisfaction scores than did those given PNB alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 22 publications
3
9
0
Order By: Relevance
“…Besides, vasovagal performance, such as dizziness, sweating, chest tightness, and shortness of breath, were closely observed. Visual analogue scale (VAS, 0, none; 10, intolerable pain) [ 11 ] and visual numeric scale (VNS, 0, terrible; 4, perfect) [ 12 ] were used to evaluate pain and quantify satisfaction.…”
Section: Methodsmentioning
confidence: 99%
“…Besides, vasovagal performance, such as dizziness, sweating, chest tightness, and shortness of breath, were closely observed. Visual analogue scale (VAS, 0, none; 10, intolerable pain) [ 11 ] and visual numeric scale (VNS, 0, terrible; 4, perfect) [ 12 ] were used to evaluate pain and quantify satisfaction.…”
Section: Methodsmentioning
confidence: 99%
“…REMI infusion by syringe pump with midazolam has been administrated to offer PAS for TRUS-guided prostate biopsy and breast biopsies. [2,11] However, to the best of our knowledge, there are no data on the use of TCI of REMI with midazolam in TRUS-guided prostate biopsy under PAS. Here, we first reported that REMI Ce of 2.0 µg/mL by TCI pump with 3 to 4 mg midazolam and intrarectal lidocaine gel use provided adequate analgesia and sedation, appropriate hemodynamic conditions, acceptable adverse events (apnea with desaturation; SpO 2 88%–89%), and better surgeon satisfaction in TRUS-guided prostate biopsy under PAS as our previous research in percutaneous transluminal balloon angioplasty for dysfunctional hemodialysis fistulas.…”
Section: Discussionmentioning
confidence: 99%
“…Doğanca et al [2] reported that REMI infusion by syringe pump was successfully used in combination with midazolam in TRUS-guided prostate biopsy under PAS. [2] Until now, there is limited data on the use of TCI of REMI with midazolam in TRUS-guided prostate biopsy under PAS. In our previous study, we showed that TCI with REMI Ce of 2.0 ng/mL and 3 to 4 mg midazolam use provided appropriate hemodynamic and respiratory conditions, and sufficient analgesia and sedation under PAS in percutaneous transluminal balloon angioplasty for dysfunctional hemodialysis fistulas.…”
Section: Introductionmentioning
confidence: 99%
“…Pain was evaluated by the visual analog scale (VAS; 0, none; 10, intolerable pain), and satisfaction was quantified using a visual numeric scale (VNS; 0, terrible; 4, perfect); only integers were allowed [23, 24]. Another independent resident and the patients were ‘blinded’ to the type of anesthesia given.…”
Section: Methodsmentioning
confidence: 99%